Market legitimation in countercultural market change - Choi, Hwanho; Burnes, Bernard (Marketing Theory, 2022)
Drawing on concepts of institutional work, legitimacy, and institutional logics, we investigate why countercultural markets experience institutional change and the actions institutional work market actors perform to inform institutional logics and ensure the legitimacy of countercultural markets. Although previous research suggests market changes and disruption, little attention has been paid to markets that originate from different institutional backgrounds, changes in the market experience in relation to its legitimization, and institutional work to attain legitimacy. The case of indie music in South Korea illustrates the evolution of a cultural market from the introduction of its ethos, the crisis caused by legitimacy pressures, and the transformation of the market. Using data gathered through in-depth interviews with indie labels and music consumers in South Korea, and archival sources, our research illuminates the source of market struggle and theorizes approaches that market actors perform to overcome the struggle.
Keywords: counterculture; Institutional theory; legitimation; market dynamics; popular music